Middle Neolithic fluorites in Northern France and Belgium: characterization, sourcing and methodological limitations - Goemaere, Eric; Vanmontfort, Bart; Bonjean, Dominique; Bosquet, Dominique; Bostyn, Françoise; Cayol, Nicolas; Colas, Caroline; Collet, Hélène; Delbey, Thomas; Delye, Emmanuel; Golitko, Mark; Jadin, Ivan; et al. (Elsevier, 2023)
Ornaments and fragments of fluorite have been found at sixteen Neolithic sites in Belgium and Northern France, mainly Middle Neolithic sites associated with the Michelsberg culture and the Spiere and Chassean groups. These sites are located in a large geographical area representing different types of sites and various geological backgrounds. One of the aims of this study is to identify where this mineral could have been quarried in the Neolithic and compare the possible source(s) with those used during the Palaeolithic. A survey of some Neolithic fluorite occurrences in Belgium and Northern France was conducted and the origins of this mineral investigated by means of geochemical Rare Earth Elements and Sr-isotopic analysis. We also explore the limitations of isotopic 87Sr/86Sr and REE ratios for analysis of fluorite. Results show that Neolithic fluorite originates from different local and regional sources, mainly the Dinantian limestones/dolostones of the Ardennes Allochthon, in contrast to the use of silicified Givetian limestones of the Calestian Band near Givet (France) during the Magdalenian. The Neolithic fluorite that is studied in this paper is found exclusively at settlement sites whereas elsewhere, fluorite comes exclusively from funerary contexts.
Keywords: Fluorite ornaments; Middle Neolithic; REE; Sr isotopes; Northern France; Belgium